Computational design of microscopic swimmers and capsules: From directed motion to collective behavior. (February 2016) - Nikolov, Svetoslav V.; Shum, Henry; Balazs, Anna C.; Alexeev, Alexander
Abstract: Systems of motile microscopic particles can exhibit behaviors that resemble those of living microorganisms, including cooperative motion, self-organization, and adaptability to changing environments. Using mesoscale computational modeling, we design synthetic microswimmers and microcapsules that undergo controllable, self-propelled motion in solution. Stimuli-responsive hydrogels are used to actuate the microswimmers and to enable their navigation and chemotaxing behavior. The self-propelled motion of microcapsules on solid surfaces is achieved by the release of encapsulated solutes that alter the surface adhesiveness. These signaling solutes also enable interactions among multiple microcapsules that lead to complex, cooperative behavior. Our findings provide guidelines for creating microscopic devices and machines able to autonomously move and mimic the communication and chemotaxis of biological microorganisms. Graphical abstract: Highlights: Computational modeling points to new designs of microscopic self-propelled swimmers and capsules. Stimuli-sensitive hydrogels are used to actuate self-propelling motion of microswimmer. Catalytic microswimmers with pH sensitive bodies swarm, mimicking chemotaxis. Interaction pathways can be imposed on systems of nanoparticle-releasing capsules. Physical interactions enable design of complex cooperative behaviors in capsules.